In vitro hyperprocessing of Drosophila tRNAs by the catalytic RNA of RNase P. The cloverleaf structure of tRNA is not always stable? - Hori, Y.; Baba, H.; Ueda, R.; Tanaka, T.; Kikuchi, Y. (European Journal of Biochemistry, 2000)
We have previously reported that the catalytic RNA subunit of RNase P of Escherichia coli (M1 RNA) cleaves Drosophila initiator methionine tRNA (tRNA(Met)i) within the mature tRNA sequence to produce specific fragments. This cleavage was dependent on the occurrence of an altered conformation of the tRNA substrate. We call this further cleavage hyperprocessing. In the present paper, to search for another tRNA that can be hyperprocessed in vitro, we used total mature tRNAs from Drosophila as substrates for the in vitro M1 RNA reaction. We found that some tRNAs can be hyperprocessed by M1 RNA and that two such tRNAs are an alanine tRNA and a histidine tRNA. Using mutant substrates of these tRNAs, we also show that the hyperprocessing by M1 RNA is dependent on the occurrence of altered conformations of these tRNAs. The altered conformations were very similar to that of tRNA(Met)i. We show here that M1 RNA can be used as a powerful tool to detect the alternative conformation of tRNAs. The relationship between these hyperprocessing reactions and stability of the tRNA structure will also be discussed.